ADEQUATE MATHEMATICAL MODEL OF FUNCTIONAL RELIABILITY URBAN PIPELINE NETWORKS - , Н. И., Т. С. (Municipal economy of cities (Technical science), 2013)
The questions of organization and conduct numerical experiments to test the adequacy of the method of emergency and maintenance areas, and mathematical models built with it.